Two new species of the genus Malaxa Melichar, 1914 from China (Hemiptera, Fulgoromorpha, Delphacidae, Tropidocephalini) - Sha-Sha Lv; Hong-Xing Li; Lin Yang; Yu-Bo Zhang; Xiang-Sheng Chen (ZooKeys)
Two new species of the genus Malaxa Melichar, 1914 from Southwest China, M. chongzuoensis Lv & Chen, sp. nov. from Guangxi Zhuang Autonomous Region, and M. longispina Lv & Chen, sp. nov. from Guangdong Province, are described and illustrated. These bring the total number of species in the genus to 13, with nine recorded from China. A checklist and map of all known species of Malaxa are provided, together with an identification key for Chinese species.